Intra-aortic balloon pump entrapment and surgical removal: a case report. Issue 1 (21st August 2017) - Hardy, Niall; Starr, Neasa; Cosgrave, John; Madhavan, Prakash
Abstract: Intra-aortic balloon pump (IABP) use following myocardial infarction is now infrequent and reserved for cases of cardiogenic shock. As their use declines, so does our ability to promptly recognize and manage potential problems that may arise. A serious but rare complication of IABP insertion is balloon entrapment within the arterial tree. In this report, we share our experience of a case of balloon entrapment within the right common iliac artery and successful removal of the device via groin cut down under general anaesthesia.